Endemism among Lord Howe Island Thysanoptera, with new species of Baenothrips (Phlaeothripidae) and Scirtothrips (Thripidae) - Mound, Laurence A.; Wells, Alice (Zootaxa, 2023)
The Thysanoptera diversity of Lord Howe Island comprises 39 known species, of which 13 are considered likely to be endemic to this tiny remnant of an ancient submarine volcano. Three new species are described in Baenothrips, a small but widespread genus of wingless, fungus-feeding species in the Old World tropics. Two new species of Scirtothrips are described that are members of a species-group breeding on the youngest fronds of tree ferns.